ANALISIS SWOT PERKEMBANGAN BANK SYARIAH DI NEGARA MEGARA-NEGARA MUSLIM - Mairijani (Jurnal Hukum Islam, 2012)
The role of banks in the economic development of a nation is very vital, including Islamic banking. Therefore, this article is conducted to create an Islamic bank effectively and efficiently to compete in the global economy. This study uses SWOT analysis to provide an overview of the historical development of Islamic banks and present an analysis of the development of sharia-Islamic banks in Muslim countries.